ICT (INFORMATION AND COMMUNICATION TECHNOLOGY) USE: KAHOOT PROGRAM FOR ENGLISH STUDENTS’ LEARNING BOOSTER - Budiati Budiati (Proceedings Education and Language International Conference, 2017)
Teaching English as a second or foreign language needs variation and creativity of the teacher in order to make the class more joyful and relaxed that makes students more eager and interested in joining the class. Kahoot that is designed as a combination of ICT use in education and games is very applicable in an English classroom for boosting the students’ learning. This study discusses the use of Kahoot to boost the English students’ learning. The study is about a descriptive quantitative and qualitative research. In this case, I used Kahoot in an English classroom of DIII of Nursing consisting of 40 students to teach simple present tense. The data were collected using questionnaire before and after the instruction. The data showed the students’ feeling toward English and teaching method before and after the use of Kahoot. The result shows that after using Kahoot for teaching, the students are very interested in joining the class; they are more eager in coming to the class, they pay more attention in English and they are interested in learning more about what they had learn and want to tell others about it. Keywords: ICT (Information and Communication Technology), Kahoot, learning booster